A novel pseudocapacitance mechanism of elm seed-like mesoporous MoO3−x nanosheets as electrodes for supercapacitors. Issue 38 (16th September 2016) - Lu, Qian-Long; Zhao, Shi-Xi; Chen, Chang-Ke; Wang, Xia; Deng, Yu-Feng; Nan, Ce-Wen
Abstract : Elm seed-like mesoporous MoO3− x nanosheets were synthesised, and possess both redox and intercalation faradic pseudocapacitance mechanisms. Abstract : Pseudocapacitance is induced by surface or near surface redox, ion intercalation or underpotential deposition processes. A given electrochemically active material usually has only one of the above mechanisms. In this study, we synthesized elm seed-like mesoporous MoO3− x nanosheets, which possess both redox and intercalation faradic mechanisms. This novel pseudocapacitance mechanism causes a high capacitance of 1480 F g −1 at 5 A g −1 and outstanding cycling performance where the capacitance does not decay but increases slightly up to 10 000 cycles at a scan rate of 100 mV s −1 . Here, we clarified that the tunnel structure of MoO3− x and its special electrochemical kinetics towards H + generate this mechanism. This faradic mechanism could achieve a higher degree of utilization of the active-sites thus resulting in excellent electrochemical performance.